TUNAGRAHITA: (STUDI KASUS DI SLB YOGYAKARTA) - Junita Sipahelut (IAKN Ambon, 2021)
This research was conducted with a case study. The subject is a class II SLB student in Yogyakarta. The subject has an IQ intelligence level of 36 on the Binet Scale, which means that the subject's cognitive ability is far below that of children his age. The problems experienced by the subject can be overcome by good cooperation between parents and teachers at school. Obstacles on the subject in focusing attention and the subject's inability to write, read and the subject's inability to communicate makes the subject have to take special education in special schools (SLB) and are categorized as children with moderate mental retardation or also known as mental retardation. The intervention given to the subject is occupational therapy, while parents and teachers at school are individual counseling. The results after the intervention for 6 months, the subject was able to concentrate more, was able to recognize some letters and numbers.